Oribatid mites (Acari, Oribatida) and their seasonal dynamics in a floating bog mat in Jeziorka Kozie Reserve, Tuchola Forest (Poland) - Seniczak, Anna (Biological Letters, 2011)
The oribatid mite community from the edge of the Sphagnum mat of dystrophic K1 pond (Jeziorka Kozie Reserve, Poland), and its seasonal dynamics was studied in 2006 (29 May, 6 August and 22 October). In all seasons, Limnozetes foveolatus dominated, followed by L. ciliatus; abundant were also L. lustrum, Trhypochthoniellus longisetus, Trhypochthonius nigricans, and Trimalaconothrus foveolatus. In autumn, the mean density of Oribatida was significantly higher than in spring. The percentage of juvenile stages was generally low, but highest in summer (22%), while in the other seasons it was about half as high. Metabelba sphagni is new to the Polish fauna.